Distinct Late-Night Salivary Cortisol Cut-Off Values for the Diagnosis of Hypercortisolism - van Baal, Lukas; Wichert, Marc; Zwanziger, Denise; Dralle, Henning; Weber, Frank; Kreitschmann-Andermahr, Ilonka; Führer, Dagmar; Unger, Nicole (Hormone and Metabolic Research, 2021)
Due to high morbidity and mortality of untreated hypercortisolism, a prompt diagnosis is essential. Measurement of late-night salivary cortisol provides a simple and non-invasive method. However, thresholds and reference ranges differ among studies. The goal of this study was to define a threshold of late-night salivary cortisol for the diagnosis of hypercortisolism based on the used assay. Moreover, the influence of different aetiologies of hypercortisolism and individual comorbidities were investigated. Prospective analyses of 217 patients, including 36 patients with proven hypercortisolism were carried out. A sum of 149 patients with suspicion of hypercortisolism but negative endocrine testing and 32 patients with hypercortisolism in remission served as control group. Late-night salivary cortisol was measured using an automated chemiluminescence immunoassay. Cut-off values were calculated by ROC analysis. The calculated cut-off value for the diagnosis of hypercortisolism was 10.1 nmol/l (sensitivity 94%; specificity 84%). Only slightly lower thresholds were obtained in patients with suspected hypercortisolism due to weight gain/obesity (9.1 nmol/l), hypertension or adrenal tumours (both 9.8 nmol/l) or pituitary adenomas (9.5 nmol/l). The late-night salivary cortisol threshold to distinguish between Cushing’s disease and Cushing’s disease in remission was 9.2 nmol/l. The cut-off value for the diagnosis of ectopic ACTH-production was 109.0 nmol/l (sensitivity 50%, specificity 92%). Late-night salivary cortisol is a convenient and reliable parameter for the diagnosis of hypercortisolism. Except for ectopic ACTH-production, thresholds considering different indications for evaluation of hypercortisolism were only slightly different. Therefore, they might only be useful if late-night salivary cortisol results near the established cut-off value are present.
Keywords: Cushing’s syndrome; Cushing’s disease; late-night salivary cortisol; immunoassay